Long-term Health Effects of Malaria Exposure around Birth: Evidence from Colonial Taiwan - CHANG, Simon (Institutional Knowledge at Singapore Management University, 2014)
In the early 20th century, the Japanese colonial government initiated an island-wide malaria eradication campaign in Taiwan, resulting in not only a rapid decline in malaria across time but also elimination of disparity across regions. Exploiting variations in malaria deaths caused by the campaign, we estimate causal effects of malaria exposure around birth on the health of elderly born in the colonial period. To mitigate potential biases caused by measurement errors and omitted confounders, we employ climatic factors to instrument for malaria deaths. Our findings suggest that people who were exposed to a high malaria risk around birth tend to have a higher likelihood of cardiovascular diseases and worse cognitive functions at old age.